Real interpolation of Sobolev spaces - Badr, Nadine (MATHEMATICA SCANDINAVICA, 2009)
We prove that $W^{1}_{p}$ is a real interpolation space between $W^{1}_{p_{1}}$ and $W^{1}_{p_{2}}$ for $p>q_{0}$ and $1≤ p_{1}<p<p_{2}≤ ∞$ on some classes of manifolds and general metric spaces, where $q_{0}$ depends on our hypotheses.